2017
DOI: 10.1093/ehjqcco/qcx037
|View full text |Cite
|
Sign up to set email alerts
|

Neurological effects of proprotein convertase subtilisin/kexin type 9 inhibitors: direct comparisons

Abstract: Aims Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors considerably alter the lipid profile. We sought to examine the rates of ischaemic stroke and neurocognitive deficits in patients treated with and without PCSK9 inhibitors. Methods and results Randomized controlled trials (RCTs) reporting rates of ischaemic stroke and neurocognitive deficits in patients using PCSK9 inhibitors were identified. Standard meta-analysis techniques were used to compare these outcomes among patients treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(105 reference statements)
4
15
0
Order By: Relevance
“…Our review did not yield an increased risk for diabetes mellitus or neurocognitive events in PCSK9 inhibitor use compared to placebo in line with most published reviews [3,11,66]. One previous review showed that alirocumab had a higher risk of neurocognitive disorders.…”
Section: Non-cardiovascular Outcomessupporting
confidence: 77%
“…Our review did not yield an increased risk for diabetes mellitus or neurocognitive events in PCSK9 inhibitor use compared to placebo in line with most published reviews [3,11,66]. One previous review showed that alirocumab had a higher risk of neurocognitive disorders.…”
Section: Non-cardiovascular Outcomessupporting
confidence: 77%
“…In this study, a total of 1,204 subjects with mean age of 65 years, that did not present neurological disorders on treatment with evolocumab or placebo, were followed for 1.6 years without evidencing any association with adverse cognitive effects (Giugliano et al, 2017b). This result was further confirmed by a recent meta-analysis (Bajaj et al, 2018; Harvey et al, 2018). However, considering the short follow-up period of the EBBINGHAUS, a 5-year extension of the FOURIER trial will provide further findings on neurocognitive functions 1 .…”
Section: Pcsk9 and Alzheimer’s Disease Pathogenesissupporting
confidence: 62%
“…This may have led to a reporting bias contributing to the increase in neurocognitive deficits noted in the earlier studies and especially in the OSLER studies which were an open-label trial. 50 Notwithstanding, in order to better clarify this issue, a randomized, double-blind, placebo-controlled, multicenter study (EBBINGHAUS study) was conducted, which involved a subgroup of patients from the FOURIER trial. The EBBINGHAUS study prospectively assessed the cognitive function in 1204 patients using the Cambridge Neuropsychological Test Automated Battery.…”
Section: Pcsk9 Inhibitors and Neurocognitive Eventsmentioning
confidence: 99%
“…51 The findings of the EBBINGHAUS study were corroborated by the results of two more recent meta-analyses, which demonstrated that there was no difference in the risk of neurocognitive deficits between PCSK9 inhibitors and control groups. 50,52 In addition, no association was found between neurocognitive treatment-emergent adverse events and LDL-C<25 mg/dL. 50 Furthermore, in a very recent study, which evaluated patient-reported cognition in the entire FOURIER trial using a self-survey, it was shown that the addition of evolocumab to maximally tolerated statin therapy had no impact on patient-reported cognition after an average of 2.2 years of treatment, even among patients who achieved LDL-C levels <20 mg/dl.…”
Section: Pcsk9 Inhibitors and Neurocognitive Eventsmentioning
confidence: 99%
See 1 more Smart Citation